Online fundraising, self-image, and the long-term impact of ask avoidance - Maja Adena; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
We provide the first field evidence pointing at the role of pure self-image, inde-pendent of social image, in charitable giving. In an online fundraising campaign for a social youth project run on an opera ticket booking platform we document how individuals appear to engage in self-deception to preserve their self-image. In addition, we provide evidence on stark adverse long-run effects of the fund-raising campaign for ticket sales. “Avoiding the ask,” opera customers who faced more insistent online fundraising buy fewer tickets in the following season. Our results suggest that fundraising management should not decide in isolation about their campaigns, even if very successful. Rather broader operational concerns have to be considered.
Keywords: D64; D03; D12; C93; L31; 330; online fundraising; quasi-experiment; self-image